Fenomena Penundaan Pembagian Harta Warisan Di Kabupaten Merauke Dalam Perspektif Syariah - Susanto, Susanto; Yulia Rahman, Hendra; Al Abza, M.Thohar (Jurnal Hukum Keluarga Islam El-Qisth, 2025)
The background in this study occurs because in Merauke Regency there are many delays in the distribution of inheritance when one of their family members dies. The delay in the distribution of inheritance for many years, for various reasons. Delaying the distribution of inheritance is tantamount to withholding the rights of the heirs. This research method uses qualitative where the data collection technique is through interviews, observations and supplemented with documents from books related to the problem being studied. Based on the findings of the study, it can be concluded that the postponement of the distribution of inheritance carried out by the people of Merauke Regency is motivated by four factors, namely: (a) Discussing inheritance after the heir dies is considered a prohibition or taboo. (b) Lack of knowledge of inheritance law. (c) One of the parents is still alive. (d) Lack of deliberation between heirs.  The next finding is that the law of postponing the distribution of inheritance carried out by the people of Merauke Regency after fulfilling the rights of the deceased is haram or not justified by Islamic Sharia. Because of this, it is clear that the command is both in the Qur'an and the Hadiths of the Prophet PBUH and in Article 175 of the Compilation of Islamic Law to immediately give inheritance to anyone who is entitled to receive it